2014
DOI: 10.1016/j.numecd.2013.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake, plasma homocysteine, and repetitive element DNA methylation in the Multi-Ethnic Study of Atherosclerosis (MESA)

Abstract: Background and Aims DNA methylation of repetitive elements may explain the relations among dietary intake, hyperhomocysteinemia, and cardiovascular disease risk. We investigated associations of methyl micronutrient intake and plasma total homocysteine with LINE-1 and Alu methylation in a cross-sectional study of 987 adults aged 45–84 y who participated in the Multi-Ethnic Study of Atherosclerosis (MESA) Stress Study. Methods and Results DNA methylation was estimated using pyrosequencing technology. A 120-ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…The results of the present study showed that the methylation levels of these AS-associated genes were significantly correlated with the ratio of SAM/SAH in the ApoE -/-mice. In conclusion, FABP4, EC-SOD and MCP-1 are important in the formation and/or development of AS, and previous studies have confirmed that DNA methylation is a diagnostic biomarker of AS (51)(52)(53). On this basis, the present study analyzed the correlation between DNA methylation of FABP4, EC-SOD, MCP-1, and B1 repetitive elements and the serum SAM/SAH ratio to confirm the hypothesis that the serum SAM/SAH ratio may be a more sensitive biomarker of AS, and …”
Section: A B C Dsupporting
confidence: 59%
“…The results of the present study showed that the methylation levels of these AS-associated genes were significantly correlated with the ratio of SAM/SAH in the ApoE -/-mice. In conclusion, FABP4, EC-SOD and MCP-1 are important in the formation and/or development of AS, and previous studies have confirmed that DNA methylation is a diagnostic biomarker of AS (51)(52)(53). On this basis, the present study analyzed the correlation between DNA methylation of FABP4, EC-SOD, MCP-1, and B1 repetitive elements and the serum SAM/SAH ratio to confirm the hypothesis that the serum SAM/SAH ratio may be a more sensitive biomarker of AS, and …”
Section: A B C Dsupporting
confidence: 59%
“…Despite these findings, few studies examined the association between LINE‐1 methylation and either obesity or weight loss. In one study, participants with BMI ≥40 kg/m 2 had higher levels of LINE‐1 methylation than participants with a BMI ≤25 . As our study only examined women with an initial BMI ≥25 kg/m 2 , there was insufficient variation to make a comparable analysis.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, recent studies have demonstrated a relationship between DNA methylation and metabolic diseases, such as obesity [21]. Therefore, the methylation levels of the promoter region in the following genes IL6 , LINE1 , SERPINE1, and TNF , previously linked with this type of pathological conditions [21,31,32,33,37,38,39], were evaluated in obese subjects with SAHS, in order to examine the molecular links between resting oxygen consumption and chronic diseases. Methylation levels of IL6 and SERPINE1 were positively associated with FFM.…”
Section: Discussionmentioning
confidence: 99%
“…Several polymerase chain reaction (PCR)-based methods have been used in order to easily analyze DNA methylation from leukocytes. In this context, global DNA methylation has been assessed measuring the methylation of CpG islands in the promoter region of the long interspersed nucleotide element 1 ( LINE1 ) retrotransposon [30,31,32,33], the only active, autonomous transposable element in humans [34]. Besides, some studies have investigated the relation between methylation pattern of genes with obesity, metabolic disturbances, and aging [27,28,35,36].…”
Section: Introductionmentioning
confidence: 99%